Identification of Endogenous Sympathetic Neuron Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP): Depolarization Regulates Production and Secretion through Induction of Multiple Propeptide Transcripts - Brandenburg, Cynthia A. (J Neurosci, 1997)
The vasoactive intestinal peptide/pituitary adenylate cyclase-activating polypeptide (PACAP)/secretin/glucagon family of peptides displays numerous physiological roles in autonomic nervous system development and function. The regulated endogenous production and release of PACAP peptides in sympathetic neurons of the superior cervical ganglion (SCG) was investigated. The two posttranslationally processed forms of PACAP, PACAP27 and PACAP38, were identified in rat adult, neonatal, and cultured SCG neurons. PACAP38 levels were ∼5–10 fmol/adult SCG and ∼2 fmol/neonatal SCG; PACAP27 levels were comparable. The authenticity of peptide immunoreactivity in these tissues was verified by coelution with synthetic PACAP in reverse-phase HPLC analysis. Reverse transcription-PCR and sequence-specific hybridization revealed PACAP mRNA in adult, neonatal, and cultured SCG neurons; in situ hybridization histochemistry and immunocytochemistry localized the PACAP peptide and proPACAP mRNA to a subset of the SCG neuronal population. Basal and stimulated release of endogenous PACAP38 from cultured sympathetic neurons was established, suggesting that these peptides may function as signaling molecules at target tissues. Chronic depolarization with 40 mm potassium stimulated the PACAP secretory rate 10- to 20-fold, with concomitant increases in cellular PACAP peptide and mRNA levels. When examined using Northern analysis, depolarizing conditions not only stimulated the 2.2 kb form of PACAP mRNA, but also induced the expression of a shortened, 0.9 kb, transcript. Further reverse-transcription PCR analysis demonstrated that this smaller transcript was not identical to the unique testicular message. These studies identify PACAP38 and PACAP27 as regulated endogenous releasable peptides contributing to the functional diversity and phenotypic plasticity of the sympathetic nervous system.